Concordancing DEVELOP* at the Interpreter-mediated Press Conferences : A Corpus-based CDA on Reform and Opening-up (RoU) as an Overarching Metadiscourse Justifying China’s recent development - Gu, Chonglong (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Thanks to the pragmatist Reform and Opening-up (RoU) program initiated by Deng Xiaoping in 1978, China, the largest developing country, has witnessed decades of sustained development and is poised to overtake the United States as the largest economy in the world. RoU is a major watershed in China’s recent history, signaling the beginning of China’s rapid economic development and meteoric rise over the past few decades in the global arena. The broader RoU discourse represents an important overarching metadiscourse, legitimizing China’s miscellaneous developments and policies, economic system, style of governance, and stances for the entire post-1978 period. In particular, ‘development’ is an operative word for and a key component of the RoU, which also constitutes a central and recurring theme throughout the interpreter-mediated premier-meets-the-press conferences in China. Development studies represents a growing and interdisciplinary research area. However, it is rarely explored from a discursive perspective in political interpreting, despite the vital mediating role of interpreters. To bridge this gap, framed within the broader trends of interdisciplinary research and digital humanities, the pragmatist mixed-methods approach of corpus-based critical discourse analysis is applied to the premier-meets-the-press data (1998–2017) to explore the government-affiliated interpreters’ agency and (re)construction of China’s ‘development’ discourse over one-fifth of a century. The study reveals the interpreters’ institutional (over)alignment and frequent strengthening of Beijing’s development discourse in English at different levels using various discursive means. Discursively, this established the interpreters’ role and text ownership in (re)shaping reality, further facilitating China’s development, (re)constructing and disseminating sociopolitical knowledge, and possibly even effecting changes and transformations to the East–West power differentials as vital (re)tellers of the Chinese story. Looking beyond the traditional view of interpreting as a more static and mechanical process in a semi-closed and self-contained system, this article discusses the vital role interpreting plays from a historical, communication, geopolitical and development perspective.